Potential pollinators and robbers: a study of the floral visitors of Heliconia angusta (Heliconiaceae) and their behaviour - Stein, Katharina; Hensen, Isabell (Journal of Pollination Ecology, 2011)
Floral syndromes are traditionally thought to be associated with particular pollinator groups. Ornithophilous flowers tend to have traits that facilitate bird pollination such as having long, narrow, tubular corollas, often vivid coloration and diluted, sucrose-rich nectar. However, recent studies have shown that flowers attract a broader spectrum of visitors than might be expected. Furthermore, the classification of floral visitors as ‘robbers’ or ‘pollinators’ often is not as simple as it seems, as pollinators can at times act as robbers and vice versa. We studied the species composition, behaviour and ecology of floral visitors, including potential pollinators and robbers, of Heliconia angusta (Heliconiaceae), an endemic understory herb of the Atlantic Rainforest of Brazil. In addition, the impact of the plant inflorescence attractiveness and of weather and light conditions on visitor abundance and frequency was investigated. Flower visitors were found to be scarce with a total of only 151 visits being observed during 120 h of field observations. A stingless bee species (Trigona sp.) appeared to be the most abundant visitor to the ornithophilous flowers of H. angusta, along with four different species of hummingbirds and two species of butterflies. We consider Trigona sp. rather as pollen robber, but which still has the potential to be a secondary pollinator, whereas the hummingbirds were the principle legitimate visitors. Most flower visitors were recorded between 9.00 am and 1.00 pm with a higher number visiting under semi-shaded conditions than in full shade. Hummingbird numbers increased with flower abundance while the other visitor group numbers were not affected.